The Determinants of Foreign Direct Investment in Ecuador: Empirical Analysis of the Period 2002-2017 - Rivera, Mauricio (2021)
The objective of this research is to identify the determinants that stimulate foreign direct investment (FDI) in Ecuador between 2002 and 2017. Using ordinary least squares estimates and an autoregressive vector model (VAR), it is empirically verified that the degree of openness of he economy and labor productivity are positively related to FDI, which indicates that the investments of transnational companies (TNCs) are oriented towards the strategy of seeking markets and efficiency. Meanwhile, gross domestic product, inflation, the real exchange rate, and labor cost were less important